Treatment Indications of Carbon Solution-Assisted Nd:YAG Laser According to Patient Satisfaction: A Retrospective Study - Hüray Hügül; Defne Özkoca; Murat Kirişçi; Zekayi Kutlubay (Dermatology Practical & Conceptual, 2023)
Background: Carbon solution-assisted Nd:YAG lasers were previously used in enlarged pores; hair removal; acne and acne scars; and facial rejuvenation.